Bullying e dislexia: um estudo a partir do preconceito nas escolas públicas - Santos, Igor Henrique Farias (2019)
The aim of this research was to investigate the characterization of bullying in schools in Grande Aracaju and its occurrence against students considered to be in a situation of inclusion, specifically, in those who live with dyslexia. In chapter 1, an integrative review, we sought to analyze the scientific productions on specific learning disorders (SLD), identify how this life condition is represented in the school environment and verify the association of this theme with the phenomenon of prejudice and bullying. The searches took place in the scientific databases of the Web of Science, Scopus, SciELO and LILACS, using the descriptors "specific learning disorder", "school environment", "prejudice" and "bullying", resulting in 13 articles, published between 2008-2018. The results showed that TEAp are perceived by their limitations and difficulties, as well as the relative scarcity of works that related bullying to learning disorders, which, in their majority, highlighted dyslexia. In chapter 2, a book chapter, we sought to investigate the degree of inclusion in public schools in Grande Aracaju from the management team and 9th grade students, in order to compare educational institutions and verify the manifestations school violence against students in situations of inclusion. For this purpose, two questionnaires were used with the principals to characterize the schools and identify the degree of inclusion in them and, with the students, the scales of manifestation of prejudice and self-indication of bullying were applied. The results indicated a high degree of school inclusion in five teaching centers, a difference in the manifestation of prejudice between schools with low and high degree of inclusion, dependence between lower frequency of bullying and higher level of school inclusion, as well as the presence of a greater manifestation of prejudice against people considered fragile and with special educational needs. In chapter 3, 24 teachers participated, responsible for the subjects of Portuguese Language, Physical Education and Arts. In this, the objective was to characterize bullying through the teachers' discourse, verifying the causes, who practices, who suffers and what is necessary to fight it. From the results, the presence of the naturalization of bullying in the school environment was perceived, its practice being open to any student, while the targets are usually those whose characteristics are out of line with the social standard. The strategies indicated are in line with multidisciplinary actions involving teachers, employees, family members, students and society. Finally, in chapter 4, this time with 12 teachers, the occurrence of bullying and prejudice in dyslexic students was investigated, as well as the knowledge that teachers had about dyslexia and their attitudes and strategies in this context. The results identified that dyslexic students suffer more bullying and prejudice compared to the others, as well as that there is a lack of knowledge about dyslexia on the part of these professionals and their attitudes and strategies are more intuitive than assertive. In general, from the results obtained around this research, it was possible to expand studies in the field of prejudice, bullying, dyslexia and inclusive education. It was identified that schools need greater care with the practices of violence among their students, especially against those considered to be in a situation of inclusion. As well, there was little knowledge on the part of educators about the needs of students with some special educational need.